Developing Indicators to Assess Financial Income Sustainability of Higher Education Institutions in Vietnam - Hung Hiep, Pham; Nghia, Le Trong (VNU Journal of Science: Policy and Management Studies, 2021)
Under the context of massification and enhanced autonomy of higher education, the trend of higher education institutions to proactively seek new financial income apart from the two traditional ones, i.e. governmental allocation and tuition fee, is inevitable. This, indeed, is paramount and contributes to the sustainable development of higher education institutions. In this study, based on international practices and experiences, indicators were developed to assess sustainability of financial income at higher education institutions in Vietnam. These indicators are composed of two constituents: (i) HHI – an indicator that assesses the relative financial sustainability of a higher education institution; and (ii) RPS – an indicator that assesses the absolute financial sustainability of a higher education institution. These indicators may be employed as a state governance instrument to monitor higher education institutions, or may also be used as an institutional instrument to monitor the sub-units. Keywords Biosphere reserves, management, status and challenges, resources for management. References [1] The Government, Government Resolution No 14/2005/NQ-CP on Substaintial and Comprehensive Renewal of Vietnam’s Tertiary Education in the 2006-2020 period, [Online], https://thuvienphapluat.vn/van-ban/Giao-duc/Nghi-quyet-14-2005-NQ-CP-doi-moi-co-ban-va-toan-dien-giao-duc-dai-hoc-Viet-Nam-giai-doan-2006-2020-5013.aspx, 2005 (in Vietnamese) (Accessed on: September 15th 2020) [2] National Assembly of Vietnam, Law on Higher Education, [Online], https://thuvienphapluat.vn/van-ban/giao-duc/Law-No-08-2012-QH13-on-higher-education-143159.aspx, 2012 (in Vietnamese) (Accessed on: September 17th 2020) [3] National Assembly, Law on Amendments to the Law on Higher Education (Law No.34/2018/QH14).” [Online], https://www.economica.vn/Content/files/LAW%20%26%20REG/Law%20on%20Amendment%20to%20Law%20Higher%20Education%202018.pdf, 2018 (in Vietnamese) (Accessed on: September 15th 2020) [4] S. Lai, H. H. Pham, H. K. Nguyen, T. C. Nguyen, and A. V. Le, Toward Sustainable Overseas Mobility of Vietnamese Students: Understanding Determinants of Attitudinal and Behavioral Loyalty in Students of Higher Education, Sustainability, Vol. 11, No. 2, p. 383, Jan. 2019, doi: 10.3390/su11020383. [5] S. P. Sazonov, E. E. Kharlamova, I. A. Chekhovskaya, and E. A. Polyanskaya, Evaluating Financial Sustainability of Higher Education Institutions, Asian Soc. Sci., Vol. 11, No. 20, Jun. 2015, doi: 10.5539/ass.v11n20p34. [6] J. Salmi, Scenarios for Financial Sustainability of Tertiary Education, in Higher Education to 2030. vol. 2. Globalisation, OECD’s Centre for Educational Research and Innovations, 2009, pp. 285–322. doi: 10.1787/9789264075375-12-en. [7] N. N. N. Ahmad, S. Ismail, and S. A. Siraj, Financial sustainability of Malaysian Public Universities: Officers’ Perceptions, Int. J. Educ. Manag., Vol. 33, No. 2, pp. 317–334, Feb. 2019, doi: 10.1108/IJEM-06-2017-0140. [8] S. Rhoades, The Herfindahl-Hirschman Index, Fed. Reserve Bull., Vol. 79, No. 3, pp. 188–189, 1993. [9] G. L. Chikoto, Q. Ling, and D. G. Need, The Adoption and Use of the Hirschman–Herfindahl Index in Nonprofit Research: Does Revenue Diversification Measurement Matter?, Volunt. Int. J. Volunt. Nonprofit Organ., Vol. 27, No. 3, pp. 1425–1447, 2016, doi: https://doi.org/10.1007/s11266-015-9562-6. [10] G. L. Chikoto, Q. Ling, and D. G. Neely, The Adoption and Use of the Hirschman–Herfindahl Index in Nonprofit Research: Does Revenue Diversification Measurement Matter?, Volunt. Int. J. Volunt. Nonprofit Organ., Vol. 27, No. 3, pp. 1425–1447, Jun. 2016, doi: 10.1007/s11266-015-9562-6. [11] M. Garland, How Vulnerable Are You? Assessing the Financial Health of England’s Universities, Perspect. Policy Pract. High. Educ., Vol. 24, No. 2, pp. 43–52, Apr. 2020, doi: 10.1080/13603108.2019.1689374. [12] H. P. Tuckman and C. F. Chang, A Methodology for Measuring the Financial Vulnerability of Charitable Nonprofit Organizations, Nonprofit Volunt. Sect. Q., Vol. 20, No. 4, pp. 445–460, Dec. 1991, doi: 10.1177/089976409102000407. [13] J. S. Greenlee and J. M. Trussel, Predicting the Financial Vulnerability of Charitable Organizations, Nonprofit Manag. Leadersh., Vol. 11, No. 2, pp. 199–210, 2000, doi: 10.1002/nml.11205. [14] J. A. Kerlin, U.S.-Based International Ngos and Federal Government Foreign Assistance: Out of Alignment?, In Nonprofits and Government: Collaboration and Conflict, E. Boris and E. Stueurle, Eds. Washington, DC: The Urban Institute Press, 2006, pp. 373–398. [15] E. Nauenberg, M. Alkhamisi, and Y. Andrijuk, Simulation of a Hirschman–Herfindahl Index without Complete Market Share Information, Health Econ., Vol. 13, No. 1, pp. 87–94, Jan. 2004, doi: 10.1002/hec.814. [16] P. D. Owen, M. Ryan, and C. R. Weatherston, Measuring Competitive Balance in Professional Team Sports Using the Herfindahl-Hirschman Index, Rev. Ind. Organ., Vol. 31, No. 4, pp. 289–302, Dec. 2007, doi: 10.1007/s11151-008-9157-0. [17] S. A. Frick and A. Rodríguez-Pose, Change in Urban Concentration and Economic Growth, World Dev., Vol. 105, pp. 156–170, May 2018, doi: 10.1016/j.worlddev.2017.12.034. [18] D. D. Laura, E. P. Susana, and F. Z. Ana, European University Funding and Financial Autonomy: A Study on the Degree of Diversification of University Budget and the Share of Competitive Funding, 2011. doi: 10.2791/55199. [19] А. Firsova, Y. Preobrazhenskiy, and A. Vavilina, Inequality of Spatial Development of Higher Education in Russia, 2019. doi: 10.2991/cesses-19.2019.18. [20] W. Kenton, Revenue Per User (RPU), Investopedia [Online],https://www.investopedia.com/terms/r/rpu.asp#:~:text=Revenue per user (RPU) is,is across the customer base, 2019 (Accessed on: September 17th 2020). [21] V. Kumar, R. Venkatesan, and W. Reinartz, Performance Implications of Adopting a Customer-Focused Sales Campaign, J. Mark., Vol. 72, No. 5, pp. 50–68, Sep. 2008, doi: 10.1509/jmkg.72.5.050. [22] M. Spychalska-Wojtkiewicz, The Relation between Sustainable Development Trends and Customer Value Management, Sustainability, Vol. 12, No. 14, p. 5496, Jul. 2020, doi: 10.3390/su12145496. [23] Higher Education Statistics Agency, Higher Education Statistics Agency, 2020, [Online], https://www.hesa.ac.uk/ (Accessed on: September 19th 2020). [24] National Center for Charitable Statistics, National Center for Charitable Statistics, 2020, [Online], https://nccs.urban.org/ (Accessed on: September 19th 2020). [25] Ministry of Education and Training, Circular No. 09/2009/TT-BGDĐT on Public Implementation for Education Institutions on National Education System [Online], https://thuvienphapluat.vn/van-ban/giao-duc/Thong-tu-09-2009-TT-BGDDT-quy-che-cong-khai-co-so-giao-duc-he-thong-giao-duc-quoc-dan-89997.aspx, 2009 (in Vietnamese) (Accessed on: October 25th, 2020) [26] Pham Phu, Investment and Cost sharing in Higher Education in Vietnam, [Online], https://giaoduc.net.vn/giao-duc-24h/dau-tu-va-chia-se-chi-phi-trong-giao-duc-dai-hoc-post169522.gd, 2010 (in Vietnamese) (Accessed on: September 19th 2020). [27] M. H. Nguyen, H. H. Pham, and T. T. Le, Using the Matching Method to Calculate Service Price for Vietnam’s Higher Education (in Vietnamese), Journal of Finance, Vol. 659, No. 2, pp. 112–114, 2018.